2016
DOI: 10.1016/j.jmb.2016.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Interaction Network of Key Proteins Involved in Histone mRNA Generation: A Hydrogen/Deuterium Exchange Study

Abstract: Histone pre-mRNAs are cleaved at the 3′ end by a complex that contains U7 snRNP, the FLICE-Associated Huge protein (FLASH) and Histone pre-mRNA Cleavage Complex (HCC) consisting of several polyadenylation factors. Within the complex, the N-terminus of FLASH interacts with the N-terminus of the U7 snRNP protein Lsm11 and together they recruit the HCC. FLASH through its distant C-terminus independently interacts with the C-terminal SANT/Myb-like domain of Nuclear Protein, Ataxia-Telangiectasia locus (NPAT), a tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…This α-helical fold might also extend to residues 53–70, encompassing the LDLY motif, but this region is unlikely to contribute to the dimerization interface. Our data are consistent with recent H/D exchange studies [ 33 ], which showed that residues 75–136 underwent slow H/D exchange, indicative of extensive secondary structure in this region. Residues 58–62 exchanged significantly faster than the 75–136 region but slower than the directly surrounding sequences, suggesting the presence of a more dynamic secondary structure in the vicinity of the LDLY motif [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This α-helical fold might also extend to residues 53–70, encompassing the LDLY motif, but this region is unlikely to contribute to the dimerization interface. Our data are consistent with recent H/D exchange studies [ 33 ], which showed that residues 75–136 underwent slow H/D exchange, indicative of extensive secondary structure in this region. Residues 58–62 exchanged significantly faster than the 75–136 region but slower than the directly surrounding sequences, suggesting the presence of a more dynamic secondary structure in the vicinity of the LDLY motif [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…That Lsm11 interacts with a FLASH dimer is also consistent with the data from H/D exchange experiments. While the region between amino acids 100–120 showed the slowest H/D exchange within the entire FLASH NTD (which we show here can form a dimer), this region underwent slower H/D exchange in the presence of Lsm11 and the reduced rate of exchange extended to amino acid 130 in FLASH [ 33 ]. Since H/D exchange occurs when hydrogen bonds are temporarily destabilized, this region of FLASH (residues 100–130) is in a more stable structure in the heterotrimer than in the homodimer.…”
Section: Discussionmentioning
confidence: 99%
“…Taking advantage of our knowledge of the molecular interactions of HLB components, 44,70,72,73,[99][100][101] we have performed genetic studies in Drosophila using mutant proteins that are either processing defective or unable to localize to the HLB. Unlike other metazoan genes, where transcription can continue well 3 0 of the polyadenylation site, transcription termination is tightly coupled to histone mRNA processing in both Drosophila and mammals.…”
Section: Hlb Functionmentioning
confidence: 99%
“…Detailed in vitro binding studies demonstrated that the C-terminal Myb-like domain of FLASH also binds to Lsm11 adjacent to the binding site on Lsm11 for the N-terminus of FLASH, and that this interaction prevents FLASH binding to NPAT. 99 Thus, it is tempting to speculate that reorganization of the Lsm11-FLASH-NPAT interactions in the HLB may be part of U7 snRNP activation and the onset of RD histone premRNA processing during S phase. This idea also suggests that different pools of molecules may exist within the HLB.…”
Section: Knockdown Of Y3mentioning
confidence: 99%
“…1A). It is unclear whether the holo-U7 snRNP contains all subunits necessary for processing and whether its assembly is regulated during the cell cycle, with FLASH binding Lsm11 during the G1/S transition, as suggested by Skrajna et al (2016).…”
Section: Introductionmentioning
confidence: 99%